The efficiency of conventional microscopic selection is comparable to the hyaluronic acid binding method in selecting spermatozoa for male infertility patients - Meng-Ting Huang; Robert Kuo-Kuang Lee; Chung-Hao Lu; Ying-Jie Chen; Sheng-Hsiang Li; Yuh-Ming Hwu (Elsevier, 2015)
Objective: To evaluate if hyaluronic acid (HA)-bound spermatozoa surpassed conventional microscopy-selected spermatozoa in the status of sperm DNA integrity by acridine orange (AO) fluorescence staining. Materials and methods: Spermatozoa obtained from couples with indication for the intracytoplasmic sperm injection (ICSI) procedure due to male infertility (n = 34) and control males with normal sperm parameters (n = 12) were analyzed using AO fluorescence staining after density-gradient centrifugation (DGC), polyvinylpyrrolidone (PVP)-microscopic selection, and HA-binding selection to determine sperm DNA integrity. Results: Percentages of DNA intact spermatozoa with green fluorescence were significantly higher in both PVP-microscopic selected spermatozoa (82.1 ± 24.0%) and HA-bound spermatozoa (83.9 ± 21.1%) than in spermatozoa prepared by DGC (66.8 ± 24.0%). However, there was no significant difference between the PVP-sperm and HA-sperm groups. When the percentage of green fluorescent spermatozoa prepared by DGC fell initially below 68%, both PVP-microscopic and HA-binding selection failed to select over 90% spermatozoa with intact DNA for ICSI in the male infertility group. Compared to control males with normal sperm parameters (99.3 ± 1.8%), the proportion of green fluorescence sperm after HA-binding selection from couples with male infertility (83.9 ± 21.1%) did not reach the range of > 99% reported by Yagci et al. Conclusion: The percentages of DNA intact spermatozoa between the PVP-sperm and HA-sperm groups were not significantly different. In an ICSI procedure, a well-trained embryologist will have the same ability to choose sperm with intact DNA by conventional microscopic selection as with HA-bound spermatozoa selection.